PENGARUH KUALITAS PRODUK, ELECTRONIC WORD OF MOUTH, DAN HARGA TERHADAP MINAT BELI MOBIL WULING ALMAZ DI JABODETABEK - Ahmad Alwi, (2023)
Vehicles have now become a necessity for society in carrying out daily activities, especially four-wheeled vehicles, this has encouraged companies to compete in making the best car for the company. This research was conducted with the aim of analyzing the influence of product quality, electronic word of mouth, and price on purchase intention in Wuling Almaz car products in Jabodetabek. This research is quantitative research and the sample that has been determined is people who are active in the Jabodetabek area with a sample size of 100 respondents. The sampling technique was carried out using non-probability sampling with a purposive sampling method. Data was collected using a questionnaire and analysis was carried out using the SmartPLS 4.0 application. The results of this research show that: (1) Product quality has a significant and positive effect on purchase intention, (2) electronic word of mouth has a positive and significant effect on purchase intention, and (3) price has no significant effect on purchase intention.